A Rare case of bear attack on the face and the treatment in a tertiary hospital in Central Nepal - Singh, Ashutosh Kumar; Dulal, Sanad; Mayya, N Jayaprakasha (Journal of College of Medical Sciences-Nepal, 2015)
This case report presents a case of wild bear attack in the central region of Nepal causing extensive maxillofacial injuries and its management. The patient suffered bilateral comminuted midface fractures with extensive soft tissue lacerations. Management included multidisciplinary approach including maxillofacial surgeons, ENT surgeons and cosmetic surgeon to realign the injured soft tissue and bone to pre injury state. Outcome was satisfactory given the initial presentation of patient. JCMS Nepal. 2015; 11(2):31-33